6.7k views
1 vote
Solve using substitution method y=2x-44x-2y=-2

User Boendal
by
6.2k points

1 Answer

2 votes

Substituting the first equation in the second one we get:


4x-2(2x-4)=-2.

Applying the distributive property to the above equation we get:


\begin{gathered} 4x-2\cdot2x-2\cdot(-4)=-2, \\ 4x-4x+8=-2. \end{gathered}

Adding like terms we get:


8=-2.

The above result is a contradiction, therefore the system has no solutions.

Answer: The given system of equations has no solutions.

User Rich Shealer
by
5.7k points